Pelatihan berbasis Psikologis untuk Meningkatkan Penerimaan Diri pada Orang yang Pernah Mengalami Kusta (OYPMK) - Tutut Chusniyah; Dhelya Widasmara; Rakhmaditya Dewi Noorrizki; Mohammad Bisri; Moch. Yunus; Ika Andrini Farida; Agung Minto Wahyu; Tasya Yuni Ariskasari (Universitas Lancang Kuning, 2022)
As one of the countries with the highest prevalence of leprosy sufferers, this problem must be seriously addressed. So far, most of the treatment is still done on the medical aspect, but not much has been done to shape the psychology of the patients or OYPMK. Therefore, it is necessary to do real interventions that help from the psychological side of the patient or OYPMK. This service method uses psychological-based training, which includes several activities, namely opening, initial assessment, introduction, recognizing self-potential, forming positive perceptions, introduction to time management, increasing fighting power, training evaluation, and closing. As a result, this training has succeeded in achieving the goals set for each activity. In addition, the participants also gave testimonies of positive changes in their self-acceptance. Thus, this training activity can be a structured guideline for partners who want to implement it.